1990
DOI: 10.1073/pnas.87.14.5273
|View full text |Cite
|
Sign up to set email alerts
|

An insulin response element in the glyceraldehyde-3-phosphate dehydrogenase gene binds a nuclear protein induced by insulin in cultured cells and by nutritional manipulations in vivo.

Abstract: Two independent cis-acting insulin response elements (IREs) in the gene encoding glyceraldehyde-3-phosphate dehydrogenase [D-glyceraldehyde-3-phosphate: NAD+ oxidoreductase (phosphorylating), EC 1.2.1.12], designated IRE-A and IRE-B, are sufficient to direct insulininducible gene expression. Using the electrophoretic mobility shift assay, a 4-fold increase in the amount of IRE-A DNA bound to nuclear proteins was detected when extracts isolated from insulin-stimulated differentiated 3T3-L1 cells or from the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 18 publications
4
85
0
Order By: Relevance
“…Various cis-acting sequences that mediate insulindependent regulation of transcription have been reported in promoters of genes encoding phosphoenolpyruvate carboxykinase (PEPCK) [45], c-fos [51,52], amylase [53], glyceraldehyde 3-phosphate dehydrogenase (GAPDH) [54,55], glugacon [56,57], malic enzyme [58], delta 1-crystallin [59], prolactin [60], b-actin [61], insulin-like growth factor I-binding protein [62], tyrosine aminotransferase [46], thyrotropin receptor [63] and fatty acid synthase [64]. There seems to be no unique sequence found so far to mediate the effects of insulin.…”
Section: Resultsmentioning
confidence: 99%
“…Various cis-acting sequences that mediate insulindependent regulation of transcription have been reported in promoters of genes encoding phosphoenolpyruvate carboxykinase (PEPCK) [45], c-fos [51,52], amylase [53], glyceraldehyde 3-phosphate dehydrogenase (GAPDH) [54,55], glugacon [56,57], malic enzyme [58], delta 1-crystallin [59], prolactin [60], b-actin [61], insulin-like growth factor I-binding protein [62], tyrosine aminotransferase [46], thyrotropin receptor [63] and fatty acid synthase [64]. There seems to be no unique sequence found so far to mediate the effects of insulin.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose and insulin regulate expression of the apoA1 gene in the liver (Murao et al 1998) through an insulin response core element (IRCE) located in the 5 -flanking region of the rat apoA1 gene. The IRCE present in the apoAI promoter is related to the IRCEs identified in the G3PDH gene and glucagon gene (Nasrin et al 1990, Philippe 1991. This process may have a role in reducing apoA1 mRNA expression in diabetic animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it is differentiation-dependent since it occurs in mature adipocytes but not in pre-adipocytes [69]. Thirdly, both stable and transient transfection experiments in 3T3 adipocytes and hepatoma cells demonstrated that insulin stimulates transcription from the GAPDH promoter [71,72]. Run-on experiments showed that the insulin effect occurs within 30 min and results from an increase in the transcription rate [71].…”
Section: Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%
“…Study of the proteins that bind to IRE-A revealed that a protein, IRP-A, was induced in insulin-treated adipocytes as well as in liver upon refeeding after fasting. IRP-A binds to the 5' half of IRE-A and recognizes the CCCGCCTC core sequence [72]. By screening an expression library prepared from rat adipocytes with an IRE-A oligonucleotide, Nasrin et al [73] …”
Section: Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%